Comparison of intravitreal anti-VEGF agents and oral carbonic anhydrase inhibitors in the treatment of cystoid macular edema secondary to retinitis pigmentosa - Liang, Jia; Wu, Xueping; Chen, Lu; Feng, Lujia; Hei, Xiangqing; Diao, Yingying; Ji, Yuke; Zheng, Huiyan; Zou, Zhenhua; Fang, Dong; Zhang, Shaochong (Frontiers in Pharmacology, 2024)
To compare the efficacy of anti-VEGF agents with oral CAIs in treating cystoid macular edema (CME) secondary to retinitis pigmentosa (RP).METHODS:This retrospective study analyzed 98 patients (98 eyes) with RP-CME: 47 (48.0%) received intravitreal anti-VEGF agents and 51 (52.0%) were treated with oral CAIs. Medical records were reviewed to BCVA, CMT, and IOP at baseline and at 1, 3, 6, and 12 months post-treatment using Generalized Estimation Equations.Adverse events and risk factors influencing visual prognosis were also evaluated.Both groups showed significant improvement in BCVA and reduction in CMT at 1 and 3 months post-treatment compared to baseline (all p < 0.001). In the oral CAIs group, these improvements persisted until 6 months. However, by 12 months, neither group exhibited significant improvements in BCVA or CMT compared to baseline (all p > 0.05). Intragroup comparisons revealed that the oral CAIs group had significantly better BCVA and CMT improvements at 3 and 6 months than intravitreal anti-VEGF group (all p < 0.05). No significant differences were found between the two groups in BCVA and CMT at 12 months or in IOP at any time point (all p > 0.05). Subgroup analysis indicated that oral acetazolamide was more effective than methazolamide in reducing CMT and improving BCVA at 3 and 6 months (all p < 0.05).There were no significant differences in outcomes between intravitreal Ranibizumab and Bevacizumab (all p > 0.05). Correlation analysis showed that worse BCVA at 12 months was associated with older age (r = -0.202, p = 0.046),higher baseline CMT (r = 0.353, p < 0.001),poorer baseline BCVA (r = 0.579, p < 0.001), but but showed no correlation with genotype. Adverse effects from oral CAIs included tingling sensation (3.9%), altered taste (9.8%), and gastrointestinal upset (7.8%). Both intravitreal anti-VEGF agents and oral CAIs effectively improved CMT and BCVA in RP-CME patients within the first 3 months of treatment. However, oral CAIs demonstrated superior anatomic and functional improvements at 6 months. Poorer BCVA prognosis was associated with older age, higher baseline CMT, poorer baseline visual acuity. Larger, randomized clinical trials with extended follow-up periods are needed to confirm these findings.